(untitled) (INNOVATIVE ECONOMY, 2025)
Varyha D.O. COMPARATIVE ANALYSIS OF INNOVATIVE ACTIVITIES OF ENTERPRISES IN UKRAINE IN THE CONDITIONS OF GLOBALIZATION CHALLENGES Purpose. The aim of the article is to conduct a comprehensive analysis of the state, dynamics, and structural features of the innovative activity of enterprises in Ukraine from the perspective of combining macroeconomic, institutional, and microeconomic factors, as well as to assess the compliance of the national innovation trajectory with international indicators of innovative development and competitiveness in the context of military and globalization challenges. Methodology of research. The methodological basis of the study is a set of general scientific and special methods: analysis and synthesis – to generalize theoretical approaches to innovative development; comparative and rating analysis – to assess Ukraine’s position according to the Global Innovation Index, the Global Sustainable Competitiveness Index, and the Composite Innovation Index; statistical analysis – to study the dynamics of enterprises’ innovation activity, innovation costs, and R&D performance; a systematic approach – to identify the interrelationships between innovation resources, results, and the institutional environment. Findings. It has been established that the innovative activity of Ukrainian enterprises is characterized by wave-like and fragmentary dynamics, high sensitivity to macroeconomic instability and external shocks. A structural gap has been identified between the growth of formal innovation activity and the economic effectiveness of innovations, which manifests itself in the insufficient commercialization of innovative products. It has been proven that, given limited innovation resources, Ukraine demonstrates relative stability in innovation “outputs,” but is held back by the weakness of the institutional environment, infrastructure, and mechanisms for inter-firm cooperation. The positive developments of 2024 are interpreted as an adaptive effect rather than an established sustainable innovation trajectory. Originality. The analytical approach to assessing the innovation activity of enterprises has been improved by combining dynamic analysis of national statistical indicators with international indices of innovation development and competitiveness. Practical value. The results obtained can be used in the formation and adjustment of state innovation policy, the development of programs to support the innovative activity of enterprises, the development of innovative infrastructure and intersectoral cooperation in the conditions of post-war economic recovery in Ukraine. Key words: innovative entrepreneurship, globalization, development trends, state support, digitalization, enterprises, innovation ecosystems, competitiveness, innovative approaches, efficiency, structural transformation of the economy.